Field Marshal Sir Henry Wilson a political soldier - Jeffery, Keith (Oxford University Press, 2008)
Henry Wilson served as a senior military planner before and during the First World War. This biography offers a reassessment of his life, placing him firmly in the context of his times & revealing the many complexities of a controversially 'political' soldier.